Microdiscectomy and Foraminotomy in Cervical Spondylotic Myelopathy and Radiculopathy - NAKAGAWA, Hiroshi; SAITO, Koji; HAYASE, Hitoshi; TAKAGI, Yasushi; OKAZAKI, Toshiyuki; YAGI, Kenji; MURE, Hideo (Neurologia medico-chirurgica, 2018)
This study was to assess the efficacy of microdiscectomy, cage fixation, and right tranuncal foramintomy for the patients suffering from right radiulo-myelopathy. Anterior cervical foraminotomy was reported to be an effective option for the treatment of cervical degenerative radiculopathy but with the problem of recurrence. Since Hakuba reported the method of trans-unco-discal approach in 1976, it was designed as keyhole foraminotomy which was called transuncal approach, transpedicular approach or transvertebral approach. In the anterior approach, we usually use the right-sided approach because most of us are right-handed surgeons. We retrospectively investigated our patients who had the right foraminal stenosis causing radiculopathy and were treated with microdiscectomy, cage fixation, and right keyhole transuncal foraminotomy. Since 2011, 23 patients were treated with the manner. All of the 23 patients who had central canal stenosis and among the 23 patients, 8 patients showed only right radiculopathy and 15 patients showed radiculo-myelopathy. In all patients, the radiculopathy disappeared or significantly improved without any complications postoperatively. The average of VAS scores was 7.6 ± 2.2 in preoperative state, 2.8 ± 2.2 at discharge, and 1.1 ± 1.6 in 1 month after surgery. The average of follow-up time was 38.3 months and they had no recurrence of radiculopathy. We showed that this manner is effective and one option for the combined disease of right foraminal and canal stenosis and we believe that this manner is not complex and safe if we can understand the anatomy.